FLYPAPER EFFECT PADA DANA ALOKASI UMUM DAN PENDAPATAN ASLI DAERAH TERHADAP BELANJA DAERAH PADA KABUPATEN / KOTA MALANG PERIODE 2011-2016 - MOH. KHOERON YASIR (e_Jurnal Ilmiah Riset Akuntansi, 2017)
The aim of this research is to identify the Effect Of Flypaper Effect Of The Allocated Fund For Public And Local Revenue to The Local Expenditure. The object of this research is the regions and provinces in Malang Jawa Timur. The data of this research is the Regional Government Budget from 3 regional governments and one provincial government, The data was gathered from Agency of financial income and regional assets provinces Malang. Data of the application of funds allocated for pulic, local revenue and local expenditures from 2011-2017. This research also studies whether the regions and provinces Malang government who has applied decentralization starting from Januari 1, 2001 has been independent from central government’s fund. The result of this research showed that decentralization has not yet give independency in Malang province the funds that is used for paying the local expenditure was mostly taken from the central government instead of the local government. This research has revealed the flypapaer effect.